Julian between pagans and christians - Marcone, Arnaldo (Montesquieu.it, 2020)
The kind of religion that Julian wanted to restore had very little in common with classical paganism, which comprised a set of doctrines that presupposed an unprecedented systematization of theology as well as a specific moral teaching. These aspects constituted a radical innovation, whose underpinning was a project of paganism that incorporated, at least to a certain extent, some of the institutions created by the Christian Church during its recent development.